Learning from Cognitive Slips: Reflective Mentoring and Error-Driven Informal Learning in Internship Contexts - Sopingi Sopingi; Riana Nurmalasari; Hanggara Budi Utomo; Buyung Adi Dharma; Autchariya Krautharot (Universitas Negeri Semarang, 2026)
Background: In the VUCA era, internships function as critical learning spaces bridging academic preparation and professional practice, exposing students to complex cognitive demands where errors shape learning trajectories. Research urgency: While experiential and informal learning are widely discussed, limited attention has been given to how interns learn from cognitive errors, particularly attention and memory slips, and how these challenges can be addressed through internship design. Research objective: This study examines how attention and memory slips operate as cognitive thresholds in interns’ informal learning, explores the role of reflective practice in transforming these slips into adaptive learning opportunities, and proposes an integrated internship design model. Research method: A qualitative interpretivist–constructivist approach was employed involving 30 undergraduate interns across corporate, creative, and educational sectors. Data were collected through interviews, reflective journals, and field observations and analyzed using thematic analysis with cross-case comparison. Research findings: Attention slips were linked to cognitive overload and task fragmentation, while memory slips were associated with procedural disruption, fatigue, and the absence of cognitive aids. Supported by psychological safety, reflective supervision, and tools such as digital checklists, these slips became catalysts for informal learning and metacognitive regulation. Research conclusion: Attention and memory slips function as developmental thresholds that, when reflectively scaffolded, strengthen cognitive resilience, procedural fluency, and professional judgment. Research novelty: This study advances a cognitive scaffolding framework that positions attention and memory slips as interconnected triggers for reflective mentoring and error-driven informal learning in internship contexts.